Predicción del crecimiento de Pinus caribaea var. hondurensis Barr y Golf. en La Sabana, Oaxaca, México - Montero Mata, M.; Fierros González, A.M. (CATIE, Turrialba (Costa Rica), 2020)
6 páginas, ilustrado, 3 tabulaciones, 7 referencias.